The impact of industrial poverty deprivation risks to the quality of human capital in Kazakhstan - Polevoy, S.V.; Gelmanova, Z.S.; Gelashvili, N.N. (BUKETOV BUSINESS REVIEW, 2024)
Object: The main purpose of this work is to consider the deprivation risks that can lead to industrial (structural) poverty in the realities of industrial employment in Karaganda region of the Republic of Kazakhstan. Methods: The method of bibliometric analysis in VOSviewer. Methodological approaches for defining the con cepts of deprivation and poverty were considered: both of them from the perspective of the monetary approach and from the perspective of the multidimensional poverty method. Findings: Comparison between indicators of monetary approach and multidimensional poverty index in terms of definitions of deprivation, revealed the inefficiency of the monetary approach in deprivational reflection. The results of the multidimensional labor poverty index of the Karaganda region do not correspond to its high indicators of income and HDI. The causes of these deprivations were identified, the risks associated with them were reflected, and there are some given recommendations to smooth out their negative effects. Conclusions: The problem of multidimensional poverty exists in the region and undermines quality of human capital across a wide range of deprivations of its inhabitants. Risks and problems of this phenomenon are related to the actualization of workers' skills, the problem of which is strongly interrelated with vocational education problems.